2004
DOI: 10.3171/ped.2004.100.2.0187
|View full text |Cite
|
Sign up to set email alerts
|

Detection of oncogene amplifications in medulloblastomas by comparative genomic hybridization and array-based comparative genomic hybridization

Abstract: This is the first genome-wide survey of multiple oncogene amplifications involved in the development of medulloblastoma. Gains of several candidate oncogenes such as D17S1670, ERBB2, PIK3CA, PGY1, MET, and CSE1L were frequently detected. These genes may be used as molecular markers and therapeutic targets of medulloblastomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 36 publications
3
58
1
Order By: Relevance
“…We hypothesize that inactivation of the P53 pathway is one of the potential mechanisms in medulloblastoma to prevent OTX2-induced senescence. However, P53 mutation or amplification of MDM2, which inhibits P53, has been infrequently reported for medulloblastoma (20,(43)(44)(45)(46). However, PPM1D, shown to inhibit P53 in medulloblastoma, is highly overexpressed in most medulloblastoma and even amplified in some (9,(47)(48)(49).…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesize that inactivation of the P53 pathway is one of the potential mechanisms in medulloblastoma to prevent OTX2-induced senescence. However, P53 mutation or amplification of MDM2, which inhibits P53, has been infrequently reported for medulloblastoma (20,(43)(44)(45)(46). However, PPM1D, shown to inhibit P53 in medulloblastoma, is highly overexpressed in most medulloblastoma and even amplified in some (9,(47)(48)(49).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated 17p loss in 25-50% medulloblastomas, but not in AT/RT. 5,6 Rorke et al further found that the chromosomal abnormality identified in a subset of AT/RT is monosomy or contains a deletion of chromosome 22. 7 Recent studies reported that a CNS rhaboid tumor with an unbalanced 9;22 translocation leads to loss of 22q11.…”
mentioning
confidence: 99%
“…A number of proto-oncogenes in MB such as CDK6, PDGFRA, KIT and MYCL1 have been found to be amplified by array CGH. A single copy numbers gains of MET locus on chromosome 7q in 38.5% of the cases in 13 MBs (MacBabe 2006;Tong et al 2004). The Notch pathway was found to be implicated in MBs pathogenesis in a number of studies.…”
Section: Genetic Alterations and Its Corroletion With Clinicohistopatmentioning
confidence: 99%